Moral-psychological and Legal Aspects of the Evaluation of Evidence in Criminal Proceedings (Comparative Approach) - Alekseevich Antonov, Igor; Viktorovich Gavrilin, Yuriy; Viktorovich Pobedkin, Alexander; Kyarimovich Kutuyev, Eldar; Yurievich Vinogradov, Mikhail (International Journal of Engineering and Technology, 2018)
The impact of moral, psychological and legal aspects of the evaluation of evidence by the officials conducting the criminal proceedings on the attitude of society to its results is considered in this article. The comparative legal, formal-legal, and logical methods of study are used herein to prove that the evaluation of evidence as a mental activity cannot be controlled externally. At the same time, a free assessment of evidence is the only way to establish properly the circumstances in a criminal case. At the same time, the moral and psychological aspects of the evaluation of evidence are inherent characteristics of human thought and do not interfere with the establishment of truth. The conclusion is substantiated that it is possible to provide an objective evaluation of evidence only by the external criterion â€“ the moral requirements to the selection of judges, prosecutors, investigators and their upbringing, checked by the society.Â